Criminal Deterrence: Revisiting the Issue with a Birth Cohort - Tauchen, Helen; Witte, Ann Dryden; Griesinger, Harriet (The Review of Economics and Statistics, 1994)
We estimate the general deterrent effect of criminal justice resources on criminal behavior using panel data for a sample representative of young men in U.S. urban areas. Our data, which combine individual-level information on arrests and personal characteristics with aggregate information on criminal justice resources, allow us to obtain deterrence measures that reflect theoretical concepts and are of potential policy relevance. We find robust evidence of a general deterrent effect flowing from criminal justice, particularly police, resources. The nature of our data also allows us to conduct extensive exogeneity tests and to explore a number of possible 'third causes' for the deterrent effect. We find strong evidence that our deterrence variables are exogenous and no evidence that our deterrence result stems from commonly hypothesized third causes. Copyright 1994 by MIT Press.